LOS GESTOS DE LA PANTALLA TÁCTIL. CROWDSOURCING Y NEOLOGÍA - Cristina VARGA (Diversitate si Identitate Culturala in Europa, 2016)
Observing new findings and directions in the field, the present paper approaches the development of research methods in neology in Romanian. It means to explore new methods and strategies for gathering valuable linguistic material using innovative methods based on social networks communication and crowdsourcing. The main objectives of the present study, the first in a series of three on this subject, are to observe if it is possible to apply the strategies of crowdsourcing to the analysis of neologism in Romanian and to present the main findings about the presence of neologisms related to touchscreen gestures in Romanian. We think that the conclusions of the present paper will illustrate the way the native speakers of Romanian adapt and use new loan words.